Overcoming the SPS concerns of the Bangladesh fisheries and aquaculture sector: From compliance to engagement. Issue 2 (19th June 2017) - Alam, Shawkat; Tomossy, George F.
Abstract : Purpose: The purpose of this paper is to address the challenges developing countries face in attempting to balance sanitary and phytosanitary measures (SPS) health and safety measures against concerns about protectionism, illustrated by the impact of trade barriers on the fisheries and aquaculture sector in Bangladesh. The paper then provides recommendations to overcome the effects of these trade barriers. Design/methodology/approach: The author uses a close doctrinal approach for the first three parts of the paper by analysing the provisions of the World Trade Organisation (WTO) SPS Agreement and the effect of those provisions in creating domestic compliance gaps in the Bangladeshi fisheries and aquaculture sector. A qualitative approach is then adopted in suggesting potential reforms and future directions to assist the Bangladeshi fisheries and aquaculture sector overcome SPS trade barrier issues. Findings: To overcome the market access issues created by SPS trade barriers, Bangladesh and other developing countries require multilateral assistance, accommodation by trading partners and internal reforms. This includes reforming internal governance structures, improving trade participation and negotiation, increasing infrastructure investment and learning from similar countries who have improved their supply chain management. Research limitations/implications: This paper will have significant implications by contributing to law and policy reform debates involving international trade law and domestic compliance gaps. It will also assist other developing countries that experience SPS trade barriers to learn from the experience of the Bangladeshi fisheries and aquaculture sector. Practical implications: This paper has practical implications by providing recommendations for how Bangladesh can overcome SPS trade barriers and improve its market access. This will help Bangladesh integrate into the global trading system by enhancing its participation in the SPS framework. Social implications: By addressing and providing recommendations for the SPS trade barrier challenges faced by Bangladesh fishery and aquaculture sector, this paper provides a framework to improve the economic development and global competitiveness of the industry. This will contribute the gross domestic product growth and help increase the overall living standards of the people involved in the fisheries and aquaculture business in Bangladesh. Originality/value: This paper is an original work that has not been published elsewhere. It is the first time a paper has dealt with the legal, policy and compliance challenges faced by the fisheries and aquaculture sector in Bangladesh.